Eksplorasi Pendidikan Karakter Era Revolusi Industri 4.0 - Muhammad Ardy Zaini; Moch Shohib (Tarbiyatuna: Jurnal Pendidikan Islam, 2020)
Abstract: Cyber ​​technology is another term for education in the era of the industrial revolution 4.0, the emergence of artificial intelligence (IoT) by utilizing Artificial Intelligence "AI" is not impossible if the role of teachers will be replaced by AI and moral degradation, even though morals are the basic foundation of one's character. Based on this, the researcher examines cyber technology, educator analytics and character education alteration. This study uses a qualitative descriptive approach to the type of library research, which is to collect data that aims as an object of research. The technique used in data collection is by collecting library materials that are relevant to the intended object of discussion. The results show that learning in the industrial era 4.0 is actually the same as conventional learning, it's just that it is updated with a digitalization system, so that the term blended learning combines conventional learning and digital learning. The industrial era 4.0 really needs the presence of an educator, because in essence educators are not people who simply transfer knowledge, but there are still many roles and functions of educators, the most important of which is to become role models for students in character building. Character education in the Industrial 4.0 era can be applied through exemplary, Targhib (motivation), habituation and tadzkirah (warning).